Turning the Tide in Turbulent Times : Making the Most of Kenya's Demographic Change and Rapid Urbanization - World Bank (Washington, DC, 2013)
Kenya will need to navigate through another economic storm in 2011. This will reduce growth to a projected 4.8 percent, which is still substantially higher than the average of the last decade. The decade started on a bullish note for Kenya. In 2010, growth was higher than expected at 5.6 percent. If growth accelerated to 6 percent, Kenya could reach Middle Income Country status by 2019. Kenya is at the threshold of a major demographic transition and is urbanizing rapidly. Each year, Kenya will continue to grow by more than one million people, who will live longer, be better educated, and increasingly live in cities. This social and economic transformation needs to be managed well to catalyze its development impact. This report recommends that in order for Kenya to continue to prosper in 2011 it will need to maintain macroeconomic stability, and contain inflation and further increases in debt. This entails tighter monetary policies and a reduction of the fiscal deficit. If there is a need for additional expenditures in response to external shocks, reallocations seem to be the most appropriate response. Kenya can leverage its auspicious location and its role as a hub for the larger East African region by upgrading its infrastructure, creating a good business environment, and continuing with region integration. This would also position Kenya globally and generate additional exports in services and manufacturing. The report concludes that the best way to start making Kenya more competitive is to strengthen its coastal hub and to modernize the port of Mombasa.